All That Glitters Is Not Gold: A Computational Study of Covalent vs Metallophilic Bonding in Bimetallic Complexes of d10 Metal Centers—A Tribute to Al Cotton on the Tenth Anniversary of His Passing. Issue 1 (2nd January 2018) - Otten, Brooke M.; Melançon, Kortney M.; Omary, Mohammad A.
Abstract : As the tenth year that follows the premature passing of the inorganic chemistry legend F. Albert (Al) Cotton comes to a close, we provide some soul food that we believe Al would have enjoyed as he looks down upon two generations of disciples, a grandchild and two great grandchildren, in his scientific family tree. This article also represents a new tradition by which the editors of Comments on Inorganic Chemistry wish to lead by example, whereby we start publishing original research content that nonetheless preserves the journal's identity as a niche for "critical discussion of the current literature" of inorganic chemistry. Thus, we show novel demonstrations of a posteriori validation and a priori prediction of possible counterintuitive covalent M-M' bonds—after and before synthesis, respectively—contrasted with non-covalent M···M interactions of the metallophilic type in bridge-dimeric systems of d 10 metal centers. Mixing of (n + 1)s 0 /p 0 orbitals with (n)d 10 orbitals in the former heterobimetallics case—and lack thereof in the latter homobimetallics case—is hypothesized to be responsible for the presence or absence of covalency, respectively. However, we also demonstrate that the consequent d-s' and/or d-p' orbital mixing/hybridization can occur even in homobimetallic complexes that contain asymmetric bridging ligands (e.g., with -S^C- donor atoms that lead to orbital interactions between M-S and M-C fragments). Hence, the "control" metallophilic case for the hypothesized d 10 -d 10 polar-covalent bonding herein is best manifest by M2 (P^P)2 homobimetallics vis-à-vis M2 (S^C)2 embodiments. Finally, we also offer a point/counterpoint commentary to the readers to contrast factors that argue for covalency vs metallophilicity and forewarn against exaggerating the extent of covalent bonding in such d 10 -d 10 species. Thus, scrutinizing the various theoretical parameters has pointed to M-M' and M-M partially bonded S^C-bridge dinuclear d 10 complexes vis-à-vis the classic Cotton-type multiple metal-metal bond description in d 0<n<10 species. GRAPHICAL ABSTRACT: